Financial Distress, Capital Intensity, Inventory Intensity, and Its Influence on Tax Aggressiveness in Indonesia - Maeda, Aprilia Fika Putri (Jurnal KIAFE, 2024)
This study examines the effects of financial distress, capital intensity, and inventory intensity on tax aggressiveness in basic materials and chemical industry companies listed on the main board of the Indonesia Stock Exchange during the 2019–2021 period. The study employs a quantitative approach using secondary data obtained from annual reports, financial statements, and company performance summaries. The sample was selected through purposive sampling, resulting in 81 firm-year observations after outlier elimination. Tax aggressiveness was measured using the effective tax rate, financial distress was measured using the Modified Altman Z-Score, capital intensity was measured by the ratio of total fixed assets to total assets, and inventory intensity was measured by the ratio of total inventory to total assets. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing with IBM SPSS version 29. The results show that financial distress has a significant negative effect on tax aggressiveness, while capital intensity and inventory intensity have no significant effects. Simultaneously, the three independent variables significantly affect tax aggressiveness. The adjusted coefficient of determination is 7.4%, indicating that the research model explains 7.4% of the variation in tax aggressiveness.